The linguistic picture of HOME in Lemkos’ ethnolect. The analysis of vocabulary data - Misiak, Małgorzata (Slavistica Vilnensis, 2016)
The article is a part of the study into Lemkos’ concept of HOME based on the analysis of vocabulary data and selected texts. The linguistic and cultural analysis of the concept of HOME presented in the article shows that it is a crucial value for the Lemkos. ДИМ/ХЫЖА refers to not only ‘a building / house’ but, in particular, it becomes a synonym of a small lost homeland especially in the context of displacing the Lemkos. The text was written under the research project Methods of analysing the linguistic picture of the world in the context of comparative research led by professor Jerzy Bartmińki (a grant NPRH no 0132/NPRH2/H12/81/2012, The Institute of Slavic Studies, Polish Academy of Sciences).
Keywords: Lemkos’ ethnolect; the concept of home; system data